Infecciones causadas por Candida spp. Resistente al fluconazol en pacientes con el síndrome de inmunodeficiencia adquirida (SIDA). Reporte de un caso. - Moreno, José (2013)
Large, ulcerative lesions over the skin scalp, and oral mucosa were observed in a patient with acquired immunodeficiency syndrome (AIDS) receiving chronic suppressive therapy with fluconazole. Candida glabrata was recovered in culture from biopsy material, and was found to be resistant to reported frequency of infections with Candida spp. resistant to fluconazole has increased in recent years. We review the literature regardin fluconazole resistant infections in patients with AIDS, discuss the possible mechanisms of resistance, and management options.